Comparison of four different intraosseous access devices during simulated pediatric resuscitation. A randomized crossover manikin trial - Bielski, Karol (Eur J Pediatr, 2017)
The aim of the study was to compare the success rate, procedure time, and user satisfaction of pediatric NIO™ compared to Pediatric BIG®, EZ-IO®, and Jamshidi intraosseous access devices. This was a randomized, crossover manikin trial with 87 paramedics. The correct location of intraosseous access when using NIO, BIG, EZ-IO, and Jamshidi was varied and was respectively 100, 90, 90, and 90%. The time required to obtain intravascular access (time T1) in the case of NIO, BIG, EZ-IO, and Jamshidi was varied and amounted to 9 s [IQR, 8–12] for NIO, 12 s [IQR, 9–16] for BIG, 13.5 s [IQR, 11–17] for the EZ-IO, and 15 s [IQR, 13–19] for Jamshidi. The paramedics evaluated each device on the subjective ease with which they performed the procedures. The intraosseous device, which proved the easiest to use was NIO, which in the case of CPR received a median rating of 1.5 (IQR, 0.5–1.5) points. Conclusion: Our study found that NIO® is superior to BIG®, EZ-IO®, and Jamshidi. NIO® achieved the highest first attempt success rate. NIO® also required the least time to insert and easiest to operate even by novice users. Further study is needed to test our findings in cadavers or human subjects. Based on our findings, NIO® is a promising intraosseous device for use in pediatric resuscitation.